Detection and prevalence of active drug efflux mechanism in various multidrug-resistant Klebsiella pneumoniae strains from Turkey - (:unkn) unknown (AMER SOC MICROBIOLOGY, 2004)
The prevalence of active drug efflux pump and porin alterations was investigated in Turkish nosocomial strains of Klebsiella pneumoniae exhibiting a multidrug-resistant phenotype. MICs of various antibiotics, including quinolones, chloramphenicol, tetracycline, and beta-lactams, for those strains were determined either with or without the efflux pump inhibitor phenylalanine arginine beta-naphthylamide (PAbetaN). Thirty-nine percent of the strains exhibited a PAbetaN-modulated resistance for quinolones, chloramphenicol, and tetracycline. In these strains, a significant increase of chloramphenicol accumulation was gained in the presence of the efflux pump inhibitor PAbetaN or with the energy uncoupler carbonyl cyanide m-chlorophenylhydrazone. Moreover, high-level expression of the membrane fusion protein AcrA, which was immunodetected in most of those isolates, suggests that the AcrAB/ToIC efflux machinery contributed to their antibiotic resistance. Studies of K. pneumoniae porins indicated that the majority of the strains, including extended-spectrum beta-lactamase producers and efflux-positive ones, presented an alteration in their sorbitol-sensitive porin (OmpK35) expression. This is the first report showing the prominent role of active drug efflux in the antibiotic resistance of nosocomial K. pneumoniae strains from Turkey.
Keywords: PERMEABILITY BARRIERS; ANTIBIOTIC-RESISTANCE; PORIN EXPRESSION; PUMP; ENTEROBACTERIACEAE; INHIBITORS; TARGETS; ACCESS; AGENTS